PERBANDINGAN APLIKASI SERESAH DIBAKAR DAN DISERAK TANPA DIBAKAR TERHADAP PERTUMBUHAN DAN PRODUKTIVITAS TANAMAN TEBU (Saccharum officinarum L.) DI DISTRIK CINTA MANIS PT PERKEBUNAN NUSANTARA VII - A. Furqon; Anna Kusumawati (Program Studi Agroteknologi INSTIPER, 2018)
Currently there are many companies that do to handling of sugar cane litter by burning. Burninf will affect the quality of land. Litter by scattering the land will restore the nutrients into the soil. This study aims is to find out the comparison of the influence of litter applications burned and litter scattered. The study was conducted at Cinta Manis District of PTPN VII in April to June 2017. Secondary data such as plant growth and soil on treated litter treatment were obtained from Cinta Manis District Company. The soil data of litter treatment was scattered in the analysis at Chem-Mix Pratama Yogyakarta Laboratory in July 2017. The data analysis using T-Test by comparing between the two comparable values effect of the litter treatment was burnt and the litter treatment scattered to the soil and plant. The result of the analysis of variance showed no significant difference between the treatment on the parameters of stem size, stem height, stem diameter, stem weight, and cane productivity. The littered treatment of litter gave higher yield on the parameters of stem height, stem diameter, stem weight, and sugarcane productivity, compared to the treatment of litter burned. Keywords: Litter, burn, sugarcane